SUSTAINABLE DEVELOPMENT OF CROP PRODUCTION WITH ELEMENTS OF PRECISION AGRICULTURE IN NORTHERN KAZAKHSTAN - Abuova, A. B.; Tulkubayeva, S. A.; Tulayev, Y. V.; Somova, S. V.; Kizatova, M. Zh. (Entrepreneurship and Sustainability Issues, 2020)
The Agricultural Experimental Station «Zarechnoye» LLP (AES «Zarechnoye» LLP, Kostanay region, Kazakhstan) has always been the initiator of introduction and dissemination of advanced innovative technologies; in this regard, the agriculture has been identified as the basis for the introduction of digitalization elements, i.e. precision agriculture. The use of elements of the precision agriculture system by the AES «Zarechnoye» LLP, the use of modern technology equipped with an automatic driving system, a differential fertilizer application system and plant protection products ensured a guaranteed yield with high technological indicators in an extremely arid year. The obtained yield level of grain crops exceeded the average regional level by 79.7%. An economic model for the introduction of precision agriculture elements for the farm «Agrofirma Karkyn» LLP with medium technical equipment, indicating the costs of applying the developed technologies per 1 ha, was built. The analysis of economic return was carried out as a result of increased productivity with indicating the payback period. The production and economic indicators of the surveyed farm in the Kostanay region, obtained as a result of constructing financial and economic models taking into account the introduction of precision agriculture elements, are presented. Based on the constructed financial and economic models, the calculations showed that the introduction of precision agriculture elements will reduce production costs for wheat growing to 1.6 thousand tenge per 1 ha of cultivated area, or 4% of all production costs. The payback period for simulated improvements in the implementation of precision agriculture elements for the farm, while maintaining the current processing area, will be 4.4 years. The data obtained during the study can be used by agricultural producers to develop measures to increase productivity and reduce the cost of production, as well as by government agencies to improve measures of state support and regulation in the field of agriculture, aimed at digitalization, the introduction of precision agriculture elements and increasing the competitiveness of ТОО «Сельскохозяйственная опытная станция« Заречное »(ТОО« АЭС «Заречное», Костанайская область, Казахстан) всегда был инициатором внедрения и распространения передовых инновационных технологий; В связи с этим сельское хозяйство было выявлено в качестве основы для внедрения элементов цифровизации, то есть точного земледелия. Использование элементов системы точного земледелияТОО «АЭС« Заречное », использование современных технологий, оснащенных автоматической системой вождения, дифференциальное удобрение Система нанесения и средства защиты растений обеспечили гарантированный урожай при высоких технологических показателях в крайне засушливый год. Полученный уровень урожайности зерновых культур превысил средний региональный уровень на 79,7%. Экономическая модель для введения точности. Сельскохозяйственные элементы для фермы ТОО «Агрофирма Каркын» со средним техническим оснащением, с указанием затрат на применение разработанных технологий на 1 га, было построено. Анализ экономической отдачи был проведен в результате повышения производительности труда с указанием срока окупаемости. Производственно-экономические показатели обследованного хозяйства в Костанайской области, полученные в результате построены финансово-экономические модели с учетом внедрения элементов точного земледелия. На основе По построенным финансово-экономическим моделям расчеты показали, что внедрение элементов точного земледелия позволит сократить Затраты на производство пшеницы растут до 1,6 тыс. тенге на 1 га обрабатываемой площади, или 4% от всех производственных затрат. Срок окупаемости за смоделированные улучшения в реализации элементов точного земледелия для фермы при сохранении текущей обработки площадь, будет 4,4 года. Данные, полученные в ходе исследования, могут быть использованы сельскохозяйственными производителями для разработки мер по увеличению производительности труда и снижения себестоимости продукции, а также государственными органами по совершенствованию мер государственной поддержки и регулирования в область сельского хозяйства, направленная на цифровизацию, внедрение элементов точного земледелия и повышение конкурентоспособности.
Keywords: импакт-фактор 2020; скопус; дальнее зарубежье; зарубежное издание; научный журнал; точное земледелие; периодическое издание; цифровизация сельского хозяйства; процентиль 98; q1; томсон